THE STUDY OF LOW-INTENSITY PULSED ULTRASOUND INFLUENCE ON WETTABILITY OF TITANIUM DENTAL IMPLANTS’ SURFACE IN EXPERIMENTAL MODEL - S. P. Rubnikovich; I. S. Khomich; V. T. Minchenya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of experimental studies, the purpose of which was to study the effect of low-intensity pulsed ultrasound on the wettability of the surface of titanium dental implants are described. We studied 64 titanium dental implants. The control group consisted of 32 dental implants without ultra-sonication. The experimental group consisted of 32 dental implants, which were exposed to low-intensity pulsed ultrasound. Studies using low-intensity pulsed ultrasound showed that the wettability of the surface of all the experimental samples (32 dental implant) was 100 %, and the wettability of control samples (32 dental implant) was not observed. Thus the previously unknown property of low intensity pulsed ultrasound enabling the wetting of entire surface of the dental implant was discovered.